A mouse model of Bardet-Biedl Syndrome has impaired fear memory, which is rescued by lithium treatment. - Thomas K Pak; Calvin S Carter; Qihong Zhang; Sunny C Huang; Charles Searby; Ying Hsu; Rebecca J Taugher; Tim Vogel; Christopher C Cychosz; Rachel Genova; Nina N Moreira; Hanna Stevens; et al. (PLoS Genetics)
Primary cilia are microtubule-based organelles present on most cells that regulate many physiological processes, ranging from maintaining energy homeostasis to renal function. However, the role of these structures in the regulation of behavior remains unknown. To study the role of cilia in behavior, we employ mouse models of the human ciliopathy, Bardet-Biedl Syndrome (BBS). Here, we demonstrate that BBS mice have significant impairments in context fear conditioning, a form of associative learning. Moreover, we show that postnatal deletion of BBS gene function, as well as congenital deletion, specifically in the forebrain, impairs context fear conditioning. Analyses indicated that these behavioral impairments are not the result of impaired hippocampal long-term potentiation. However, our results indicate that these behavioral impairments are the result of impaired hippocampal neurogenesis. Two-week treatment with lithium chloride partially restores the proliferation of hippocampal neurons which leads to a rescue of context fear conditioning. Overall, our results identify a novel role of cilia genes in hippocampal neurogenesis and long-term context fear conditioning.